Species of Agrilus Curtis, 1825 (Coleoptera: Buprestidae) found in the Mata Atlantica and Caatinga biomes of Brazil - Enrico Ruzzier; Letizia Migliore (Revista Chilena de Entomología)
A list is presented of Agrilus species collected during research conducted within the joint program between the Laboratory of Coleoptera of the Museu de Zoologia da Universidade de São Saulo, São Paulo (Brazil) and the Department of Science of the University of Rome 3, Rome (Italy). This paper represents a first contribution of this project and is aimed at increasing the taxonomic and chorological knowledge of the genus Agrilus from Caatinga and the Mata Atlantica, with attention to the Restinga biome. A total of seven species are listed, one of which is undetermined and three are new to science and here described: Agrilus biffii n. sp., Agrilus caatinganus n. sp., and Agrilus rossoi n. sp.